The conversation matters: a qualitative study exploring the implementation of alcohol screening and brief interventions in antenatal care in Scotland - Lisa Schölin; Niamh Fitzgerald (BMC, 2019)
Abstract Background Alcohol screening and brief intervention (SBI) in antenatal care is internationally recommended to prevent harm caused by alcohol exposure during pregnancy. There is, however, limited understanding of how SBI is implemented within antenatal care; particularly the approach taken by midwives. This study aimed to explore the implementation of a national antenatal SBI programme in Scotland. Methods Qualitative interviews were conducted with antenatal SBI implementation leaders (N = 8) in eight Scottish health boards. Interviews were analysed thematically and using the 'practical, robust implementation and sustainability model' (PRISM) to understand differences in implementation across health boards and perceived setting-specific barriers and challenges. Results In several health boards, where reported maternal alcohol use was lower than expected, implementation leaders sought to optimize enquires about women's alcohol use to facilitate honest disclosure. Strategies focused on having positive conversations, exploring pre-pregnancy drinking habits, and building a trusting relationship between pregnant women and midwives. Women's responses were encouraging and disclosure rates appeared improved, though with some unexpected variation over time. Adapting the intervention to the local context was also considered important. Conclusions This is the first study to explore implementation leaders' experiences of antenatal SBI delivery and identify possible changes in disclosure rates arising from the approach taken. In contrast with current antenatal alcohol screening recommendations, a conversational approach was advocated to enhance the accuracy and honesty of reporting. This may enable provision of support to more women to prevent Fetal Alcohol Spectrum Disorders (FASD) and will therefore be of international interest.